The integration of DRTA strategy and the zoom conference for teaching reading: an action research - Sutiyono, Akhmad; Hastomo, Tommy (Universitas Lampung, 2022)
This present research aimed to investigate the integration of Directed Reading Thinking Activity (DRTA) and Zoom conference for improving students' reading comprehension. Classroom Action Research was the research design employed in this study. The independent variable was the DRTA Strategy and the dependent variable was the students' reading comprehension. There were 30 students as the subject of this study. Reading test, field notes, questionnaires, interview, and observation sheets were the instrument of research for collecting the data. The findings of pre-test and post-test mean scores showed the improvement of students' reading comprehension using the integration of DRTA Strategy and Zoom conference. Furthermore, this combination can help English learner achieve the learning target. The students can get many benefits from using this combination to study English. They also can conduct an effective teaching-learning activity in a modern way even though they are not allowed to attend the face-to-face classroom